Effect of the World Health Organization Checklist on Patient Outcomes: A Stepped Wedge Cluster Randomized Controlled Trial. Issue 5 (May 2015) - Haugen, Arvid Steinar; Søfteland, Eirik; Almeland, Stian K.; Sevdalis, Nick; Vonen, Barthold; Eide, Geir E.; Nortvedt, Monica W.; Harthug, Stig
Abstract : Objectives: We hypothesized reduction of 30 days' in-hospital morbidity, mortality, and length of stay postimplementation of the World Health Organization's Surgical Safety Checklist (SSC). Background: Reductions of morbidity and mortality have been reported after SSC implementation in pre-/postdesigned studies without controls. Here, we report a randomized controlled trial of the SSC. Methods: A stepped wedge cluster randomized controlled trial was conducted in 2 hospitals. We examined effects on in-hospital complications registered by International Classification of Diseases, Tenth Revision codes, length of stay, and mortality. The SSC intervention was sequentially rolled out in a random order until all 5 clusters—cardiothoracic, neurosurgery, orthopedic, general, and urologic surgery had received the Checklist. Data were prospectively recorded in control and intervention stages during a 10-month period in 2009–2010. Results: A total of 2212 control procedures were compared with 2263 SCC procedures. The complication rates decreased from 19.9% to 11.5% ( P < 0.001), with absolute risk reduction 8.4 (95% confidence interval, 6.3–10.5) from the control to the SSC stages. Adjusted for possible confounding factors, the SSC effect on complications remained significant with odds ratio 1.95 (95% confidence interval, 1.59–2.40). Mean length of stay decreased by 0.8 days with SCC utilization (95% confidence interval, 0.11–1.43). In-hospital mortality decreased significantly from 1.9% to 0.2% in 1 of the 2 hospitals post-SSC implementation, but the overall reduction (1.6%–1.0%) across hospitals was not significant. Conclusions: Implementation of the WHO SSC was associated with robust reduction in morbidity and length of in-hospital stay and some reduction in mortality. Abstract : Supplemental Digital Content is Available in the Text.This quantitative, systematic study used Healthcare Failure Mode Effects Analysis to identify risks in the surgical escalation of care process. Participants identified communication, staffing, and hierarchical failures as root causes of a failure to escalate. Targeted interventions based on escalation protocols, educational sessions, and staff recruitment should improve patient safety.